A budget impact analysis of bezlotoxumab versus standard of care antibiotics only in patients at high risk of CDI recurrence from a hospital management perspective in Germany - Florian Jakobs; Sebastian Marcel Wingen-Heimann; Julia Jeck; Anna Kron; Oliver Andreas Cornely; Florian Kron (BMC, 2021)
Abstract Background Clostridioides difficile infection (CDI) is one of the leading nosocomial infections, resulting in increased hospital length of stay and additional treatment costs. Bezlotoxumab, the first monoclonal antibody against CDI, has an 1 A guideline recommendation for prevention of CDI, after randomized clinical trials demonstrated its superior efficacy vs. placebo. Methods The budget impact analysis at hand is focused on patients at high risk of CDI recurrence. Treatment with standard of care (SoC) + bezlotoxumab was compared with current SoC alone in the 10 most associated Diagnosis Related Groups to identify, analyze, and evaluate potential cost savings per case from the German hospital management perspective. Based on variation in days to rehospitalization, three different case consolidation scenarios were assessed: no case consolidation, case consolidation for the SoC + bezlotoxumab treatment arm only, and case consolidation for both treatment arms. Results On average, the budget impact amounted to € 508.56 [range: € 424.85 - € 642.19] for no case consolidation, € 470.50 [range: € 378.75 - € 601.77] for case consolidation in the SoC + bezlotoxumab treatment arm, and € 618.00 [range: € 557.40 - € 758.41] for case consolidation in both treatment arms. Conclusions The study demonstrated administration of SoC + bezlotoxumab in patients at high risk of CDI recurrence is cost-saving from a hospital management perspective. Reduced length of stay in bezlotoxumab treated patients creates free spatial and personnel capacities for the treating hospital. Yet, a requirement for hospitals to administer bezlotoxumab is the previously made request for additional fees and a successful price negotiation.